PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TGT (TEAMS GAMES TOURNAMENT) DENGAN MEDIA MICROSOFT POWERPOINT UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA POKOK BAHASAN HIDROLISIS GARAM - Lisnawaty Simatupang; Wesly Hutabarat; Jiwa Dash (Jurnal Pendidikan Kimia (JPKim), 2014)
Abstract. Research application of cooperative learning TGT (Teams Games Tournament) with microsoft office powerpoint to improve student learning outcomes on the subject of salt hydrolysis has been carried out. The population in this study were all XI –IPA students of SMA N 2 Model Binjai, amounting to 8 classes and each class consists of 40 students. The samples in this study were 2 classes are taken at purposive sampling. The instrument used in this study were achievement test in the form of multiple choice questions with the amount of as much as 30 questions that have been declared valid and reliable instrument observation and student learning activities. The hypothesis was tested with a significance level of 0.05 obtained thitung ≥ ttable, is thitung = 11,348 > 1.6671, so Ho is rejected and Ha accepted. Based on data analysis and hypothesis testing conducted found that: (1) Student learning outcomes are taught with cooperative learning model TGT using microsoft office powerpoint media namely (81.925 + 39.425), and direct instruction model of learning to use the media microsoft office powerpoint (71.475 + 38,370), (2) students' learning activities using cooperative learning model TGT (Teams Games Tournament) with microsoft office powerpoint media that is higher than 81.080 direct instruction model of learning with microsoft office powerpoint media namely 55,630 (3) TGT cooperative learning model using microsoft office powerpoint media can improve student learning outcomes, (4) the percentage increase student learning outcomes using cooperative learning model TGT with microsoft office powerpoint media that is higher by 73.00% compared to direct instruction model of learning with microsoft office powerpoint media which is equal to 53.00%, (5) cognitive domains that terkembangkan after learned with TGT cooperative learning model using microsoft office powerpoint media is knowledge (C1) which is equal to 91.00% and the direct instruction model of learning using microsoft office powerpoint media is knowledge (C1) which is equal to 72.7% Kata kunci: kooperatif tipe TGT, microsoft office powerpoint, direct instruction